RISK ASSESSMENT USING THE MATRIX METHOD FOR THE JOB "POWER LINE FITTER" IN A BUSINESS ENTITY - Branko Radović; Bojana Zlatković; Anica Ranđelović (Journal of Sustainable Technologies and Materials)
The assessment of workplace hazards involves recognizing the likelihood of occurrence and the severity of potential injuries or occupational diseases to employees. The risk assessment is performed by a team of experts from various scientific and professional fields to objectively evaluate the attributive and/or numerically expressed level of risk, which will inform the employer and the employee about the extent of exposure to a harmful event. In this paper, the risk assessment of one workplace "Power line fitter" in a business entity was carried out, using the qualitative matrix method. The risk assessment for the mentioned workplace showed that it is a workplace with a medium risk of working at height, the danger of direct contact with parts of the electrical installation and live equipment, and harmful climatic influences - work in an open space, which was confirmed by the use of other risk assessment method.